PERANCANGAN STRATEGI PELAYANAN BERBASIS PENGETAHUAN PADA KANTOR NOTARIS - Sukarti Sukarti; Sri Karnila (KLIK- KUMPULAN JURNAL ILMU KOMPUTER, 2016)
The study resulted in a strategy design for certificate making service at the notary office. It was a case study at notary office of Theresia Dwi Wijayanti, S.H. the mechanism and work frame/ principle of certificate making service was still in the form of job instructions understood only by several employees, and this often made repeated questions at the service department and became a problem when the employee took permission not to come to work. Since the mechanism and work flow/ principle of the service was not vivid, and there were no any media for the service of making the authentic certificates, the mechanism and the work flow/ principles of services in making the certificates at the notary office.The design of the strategy is facilitated with the service of certificate making that could be used as a media in knowledge share, became a knowledge management portal at the service department, so it would grow knowledge share culture (Knowledge Sharing) among the employees and the optimal service to the clients.The system development method used in the study was Knowledge Management Roadmap method with these phases: business modeling, use-case modeling, analysis, design, and implementation. This method resulted in a strategy design for the service department to make certificates. Furthermore, the notary office would have a knowledge share media.Key words      : Knowledge Management, Knowledge Sharing, Knowledge Management RoadmapPenelitian menghasilkan rancangan strategi untuk pelayanan pembuatan akta pada kantor Notaris, study kasus pada kantor Notaris Theresia Dwi Wijayanti, SH. Mekanisme dan alur kerja/prinsip pelayanan pembuatan akta masih berupa instruksi kerja, yang dipahami oleh beberapa pegawai saja, dan sering menjadi pertanyaan berulang pada bagian pelayanan serta menjadi kendala pada saat pegawai izin tidak masuk kerja. Karena mekanisme dan alur kerja/prinsip pelayanan belum jelas dan belum adanya media untuk pelayanan pembuatan akta otentik, mekanisme dan alur kerja/prinsip pelayanan dalam pembuatan akta pada kantor Notaris.Rancangan strategi ini difasilitasi dengan aplikasi pelayanan pembuatan akta yang dapat digunakan sebagai media dalam berbagi pengetahuan, menjadi portal Knowledge Manajement pada bagian pelayanan, sehingga menumbuhkan budaya penyebaran pengetahuan (Knowledge Sharing) diantara pegawai dan pelayanan optimal kepada klien. Metode pengembangan sistem yang digunakan adalah Knowledge Management Roadmap dengan tahapan pemodelan bisnis, pemodelan use case, analisis, perancangan, dan implementasi. Dengan metode Knowledge Manajement Roadmap menghasilkan rancangan strategi untuk bagian pelayanan pembuatan akta dan kantor Notaris memiliki sebuah media berbagi pengetahuan.Kata kunci: Manajemen Pengetahuan, Knowledge Sharing, Knowledge Manajement Roadmap.